Competences of graduation for the curricular redesign of mechanical engineering based on local and national development agendas - F Viera, E; A Paucar, M; Reinoso, A (International Journal of Engineering and Technology, 2018)
This article proposes the implementation of CDIO (Conceive, Design, Implement and Operate) in the curricular redesign of the career of Mechanical Engineering. It presents a binding scheme of shared learning between the industry and academia to obtain graduate competencies, as a basis for curricular redesign. A new educational model is designed which allows the transition from know what to know how; interlacing the disciplines that intervene with skills and abilities to solve projects focused on local and national realities. It was defined that of the CDIO, standards 2, 3, 5 and 7 apply. This generates a student-centered curriculum with complementary disciplines, interlaced with inter and intra-personal skills, product manufacturing, processes and systems. This proposal considers specific knowledge, skills, values and attitudes that must be applied in the integral formation of Mechanical Engineers, in order to respond to the socio-productive needs of the country. Finally, the curricular redesign determines the areas of professional academic impact in Design, Energy, Materials and Production Management, taking into account the graduate competences and in a complementary way the learning results of the subjects of the career.Â Â
Keywords: Curricular Design; Learning Achievements; CDIO.